2011
DOI: 10.1002/qj.880
|View full text |Cite
|
Sign up to set email alerts
|

Improving transmission calculations for the Edwards–Slingo radiation scheme using a correlated‐k distribution method

Abstract: A new version of the Edwards-Slingo (ES) radiation scheme is developed using the correlated-k distribution (CKD) method. The work is conducted based on the line-by-line radiative transfer scheme GENLN2. A dataset of new ozone absorption cross-section in the ultraviolet spectrum and new oxygen collisioninduced continuum data have been implemented in both the GENLN2 and new ES schemes. In order to improve the efficiency of the ES scheme, a new technique is proposed in this work to optimize the k distribution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…Currently the ES radiation scheme uses a combination of the exponential sum fitting of transmissions (ESFT) technique (Wiscombe & Evans 1977) and the correlated-k method (Lacis & Oinas 1991;Goody et al 1989) to obtain k-coefficients, some details of which can be found in Sun (2011). In each band the absorption coefficients from the line-by-line wavenumber grid are reordered according to strength in increasing order and divided into n k subintervals.…”
Section: The Correlated-k Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently the ES radiation scheme uses a combination of the exponential sum fitting of transmissions (ESFT) technique (Wiscombe & Evans 1977) and the correlated-k method (Lacis & Oinas 1991;Goody et al 1989) to obtain k-coefficients, some details of which can be found in Sun (2011). In each band the absorption coefficients from the line-by-line wavenumber grid are reordered according to strength in increasing order and divided into n k subintervals.…”
Section: The Correlated-k Methodsmentioning
confidence: 99%
“…This scheme has been widely used in the meteorological community, see e.g. Sun (2011). We also describe the line-by-line discrete ordinate code Atmo used for comparisons.…”
Section: The Edwards-slingo Radiation Scheme and Atmomentioning
confidence: 99%
“…The radiative transfer scheme used in the model is a modified version of the Edwards−Slingo scheme (Edwards & Slingo 1996, Sun 2011, and uses an approach of correlated-k distribution (Fu & Liou 1992, Li & Barker 2005 for the flux calculation. The scheme has 9 spectral intervals for solar radiation (0.25 to 5.0 µm) and 8 for thermal radiation (5.0 to 40 µm).…”
Section: Radiative Transfer Schemementioning
confidence: 99%
“…The scheme has 9 spectral intervals for solar radiation (0.25 to 5.0 µm) and 8 for thermal radiation (5.0 to 40 µm). When compared with line-by-line calculations, the scheme can accurately simulate gaseous absorption due to water vapor, carbon dioxide, ozone, methane, nitrous oxide, oxygen and chlorofluorocarbons (Sun 2008(Sun , 2011. The treatment of liquid cloud optical properties adopts the works of Hu & Stamnes (1993) and Sun & Rikus (2004), and the ice cloud properties follow the work of Chou (2002).…”
Section: Radiative Transfer Schemementioning
confidence: 99%
“…The broad-band model used in this study is the Sun-Edwards-Slingo version 2 (SES2) scheme (Sun, 2011). It has 9 spectral bands in the shortwave region, 4 bands in the UV-VIS and 5 bands in the NIR.…”
Section: Radiation and Climate Modelsmentioning
confidence: 99%